Effects of physical activity interventions on strength, balance and falls in middle-aged adults: a systematic review and meta-analysis - Adams, Michael; Gordt-Oesterwind, Katharina; Bongartz, Martin; Zimmermann, Samuel; Seide, Svenja; Braun, Volker; Schwenk, Michael (Sports medicine - open, 2023)
Weak lower body strength and balance impairments are fundamental risk factors for mobility impairments and falls that can be improved by physical activity (PA). Previous meta-analyses have focused on these risk factors in adults aged ≥ 65 years. Yet, the potential of PA for improving these risk factors in middle-aged populations has not been systematically investigated. This systematic review and meta-analysis aim to examine the effect of general and structured PA on lower limb strength, postural balance and falls in middle-aged adults.
Gesehen am 14.05.2024